2011
DOI: 10.1021/jp2072827
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Structure of and Li+ Ion Solvation in Bis(trifluoromethanesulfonyl)amide Based Ionic Liquids Composed of 1-Ethyl-3-methylimidazolium and N-Methyl-N-propylpyrrolidinium Cations

Abstract: Liquid structures of the bis(trifluoromethanesulfonyl)amide based ionic liquids composed of 1-ethyl-3-methylimidazolium and N-methyl-N-propylpyrrolidinium ([C(2)mIm(+)][TFSA(-)] and [C(3)mPyrro(+)][TFSA(-)], respectively) and Li(+) ion solvation structure in their lithium salt solutions were studied by means of high-energy X-ray diffraction (HEXRD) technique with the aid of MD simulations. With regard to neat ionic liquids, a small but significant difference was found at around 3.5 Å in the intermolecular radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
121
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 104 publications
(139 citation statements)
references
References 190 publications
16
121
0
1
Order By: Relevance
“…4 The ion-ion interaction in ILs strongly depends on the composing ions (cation and/or anion), the alkylchain length of the cation and the hydrogen bonding capability to give a specific solvation environment of such solutes as metal ion, low-weight molecule and polymer in the ILs. [5][6][7][8] The miscibility of polymer and solvent IL varies as the temperature changes, and polymer/IL solutions often exhibit an upper critical solution temperature (UCST) or lower critical solution temperature (LCST) phase behavior. 9 It is well-known that poly(N-isopropylacrylamide) (PNIPAm) exhibits the LCST phase behavior at near room-temperatures in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…4 The ion-ion interaction in ILs strongly depends on the composing ions (cation and/or anion), the alkylchain length of the cation and the hydrogen bonding capability to give a specific solvation environment of such solutes as metal ion, low-weight molecule and polymer in the ILs. [5][6][7][8] The miscibility of polymer and solvent IL varies as the temperature changes, and polymer/IL solutions often exhibit an upper critical solution temperature (UCST) or lower critical solution temperature (LCST) phase behavior. 9 It is well-known that poly(N-isopropylacrylamide) (PNIPAm) exhibits the LCST phase behavior at near room-temperatures in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the addition of lithium salts into ILs significantly increases the viscosity of the mixtures because the strongly Lewis acidic Li + cations require strong coordination by the anions to form bulky ion-multiplets. [85][86][87][88] Furthermore, the Li + -transference number is low due to the presence of at least two different cations (Li + and IL cation) and one anion (the common anion of Li-salt and IL). [85][86][87][88] The Li + -conducting IL electrolytes may improve the safety issue of lithium batteries, but their performance is not good due to poor transport properties.…”
Section: © -Conducting Ils and Solvate Ilsmentioning
confidence: 99%
“…The cation-cation correlations are also found at around 8 Å in the G MD inter (r), although they are significantly weak in the intensity. This is because [C 2 mim] + is constructed by H, C, and N atoms with small X-ray scattering factor, f, unlike [FSI] − with large ones of F and S. It is thus concluded that [36] and [62] the anion-anion correlations mainly contribute to the 8.5 Å peak observed in the total G exp inter (r), whereas the cation-cation ones less contribute to the total G exp inter (r). With regard to the first neighboring cation-anion interaction, we further analyzed the MD results to evaluate space distribution function, SDF.…”
Section: Liquid Structure Of Neat Ilsmentioning
confidence: 99%